2019
DOI: 10.1002/lio2.245
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomas of the paranasal sinuses: An analysis of the SEER database

Abstract: Objective To determine the demographics, treatment modalities, and overall survival of patients with sinonasal sarcoma. Methods All cases of primary sinonasal sarcomas diagnosed between the years of 2009 and 2014 were extracted from the National Cancer Institute's Surveillance, Epidemiology, and End Results database. Additional variables collected included age, gender, ethnicity, tumor histological subtype, tumor size, treatment modality, vitality status, and follow‐up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…6 In a recent 2019 SEER (Surveillance, Epidemiology, and End Results) database review of sinonasal sarcomas, Martin et al found the 5-year OS to be just 31%. 4 This was lower than a previous SEER database study in 2012 of 352 patients with sinonasal sarcoma with a 5-year OS of 47%. 9 Our survival outcomes were more favorable than both of these reports.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…6 In a recent 2019 SEER (Surveillance, Epidemiology, and End Results) database review of sinonasal sarcomas, Martin et al found the 5-year OS to be just 31%. 4 This was lower than a previous SEER database study in 2012 of 352 patients with sinonasal sarcoma with a 5-year OS of 47%. 9 Our survival outcomes were more favorable than both of these reports.…”
Section: Discussionmentioning
confidence: 59%
“…1,2 Approximately 7% of sarcomas in the head and neck arise from the paranasal sinuses. 3,4 Patients may present with symptoms such as nasal obstruction, pain, eye complaints, or cranial nerve deficits. Treatment is typically surgical often with adjuvant radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Soft tissue sarcomas are rare tumours frequently arising in the maxillary sinus. Tumour resection with wide margins, recommended in other anatomical locations, is frequently not achievable because of the anatomical proximity of the brain and the orbit but it should always be performed when feasible [ 87 ]. The recommended wide resection is hardly ever achieved with an endoscopic approach [ 88 ].…”
Section: Surgical Strategy According To Histologymentioning
confidence: 99%
“…The most frequent histology is alveolar rhabdomyosarcoma. It is an aggressive tumor, and the 5-year overall survival is estimated at 31-62% [135][136][137]. The management of these tumors is multimodal.…”
Section: Soft Tissue Sarcomamentioning
confidence: 99%
“…The management of these tumors is multimodal. Tumor resection with wide margins, usually recommended in other localizations, is frequently not achievable because of the anatomical proximity of the brain and the orbit [135,136]. A retrospective study found that surgery is a predictive factor of complete response in sinonasal sarcoma, regardless of the resection margin quality, and it should always be performed when feasible [136], however, the recommended wide resection is rarely compatible with endoscopic surgery.…”
Section: Soft Tissue Sarcomamentioning
confidence: 99%